Otoritas Laki-Laki Dan Perempuan: Studi Penafsiran Kontekstual Abdullah Saeed terhadap Qs. an-Nisa 4: 34 - Shomad, Abdus (Alif Lam : Journal of Islamic Studies and Humanities, 2022)
The superiority of men over women often occurs because of the use of the Qur'anic argument in understanding the position of women in social life, including in their position as leaders. It can be observed and described in verse Qs. an-Nisa' verse 34. The keyword Qawwamuna is often used as an excuse and defense to explain the position of women in Islam. This happens not only in the vocabulary of verses, but also in the role of textual interpretation which forgets the context when this verse was revealed and the contextual conditions of life today. Qs. an-Nisa' verse 34 is often interpreted in contexts that are no longer relevant today. To gain a contextual understanding of "Qauwamuna" in Qs. an-Nisa: 34, researchers used Abdullah Saeed's contextual approach to the type of library research (library research). This study uses literature data (library). The main data (primary) is the work of Abdullah Saeed, namely: The 21st Century Al-Qur'an: Contextual Interpretation. The secondary data are works or writings that discuss Abdullah Saeed's contextual approach and also interpretations related to gender issues, especially those discussing Qs. an-Nisa: 34. This research produced several conclusions, including a): Abdullah Saeed's contextual interpretation methodology is a contemporary exegesis methodology that focuses only on the text of verses or the editorial verses of the Koran, but also focuses on understanding the context, (micro context, macro context, and context of social development, culture and current situation, b): Based on the analysis it was found that the words الرجل and النساء do not only refer to biology (male and female). This verse identifies the moral ideal of the Koran as a relationship of equals. With the development of today's context, both men and women have equal leadership potential.): Qs. an-Nisa:34 contains three values, namely: fundamental values, implementational values and instructional values. With this conclusion, this thesis will strengthen the role of gender interpretation studies on the one hand, and on the other hand will strengthen the importance of the paradigm of contextual interpretation of the Qur'an